Cervical cytological study in unhealthy and healthy looking cervix - Pradhan, Neelam; Giri, Kanti; Rana, Ashma (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Aim: To compare cervical cytology in women with healthy/unhealthy cervix. Methods: A prospective study on Pap smear was performed including 200 women, 100 with healthy and 100 with unhealthy cervix, attending outpatient Gynaecology clinic of the Department of Ob/Gyn TU Teaching Hospital, Kathmandu. The cytology report was compared in the two groups. Results: Cervical dysplasia was seen in 8 women with unhealthy cervix, 7 were mild and one was severe dysplasia. In the women with healthy cervix, 5 had mild and one had moderate dysplasia. Eighty two percent of women with healthy cervix and 83% of women with unhealthy cervix had non-specific inflammation. Women who were married before 20 years (p=0.04) and had higher parity (3.3 Vs 2.8) were more likely to have unhealthy cervix (p=0.03). Excessive vaginal discharge was common in women with unhealthy cervix (p=0.0009). Conclusion: Dysplasia was slightly higher among the women with unhealthy cervix in comparision to healthy cervix but the difference was not statistically significant. Hence this study emphasizes on the importance of universal screening of both the healthy and unhealthy looking cervix. Key Words: carcinoma cervix, visual screening, Pap smear, cervical cytology, cervical dysplasia doi:10.3126/njog.v2i2.1454 N. J. Obstet. Gynaecol 2007 Nov-Dec; 2 (2): 42 - 47